A symptom‐based model to predict colorectal cancer in low‐resource countries: Results from a prospective study of patients at high risk for colorectal cancer. Issue 13 (12th April 2018) - Alatise, Olusegun Isaac; Ayandipo, Omobolaji O.; Adeyeye, Ademola; Seier, Ken; Komolafe, Akinwunmi O.; Bojuwoye, Matthew O.; Afuwape, Oludapo O.; Zauber, Ann; Omisore, Adeleye; Olatoke, Samuel; Akere, Adegboyega; Famurewa, Olusola; et al.
Abstract : BACKGROUND: Colorectal cancer (CRC) rates in low‐resource countries, which typically lack CRC screening programs, are rising. This study determined whether a risk model for patients with rectal bleeding could identify patients with curable CRC. METHODS: This prospective, cross‐sectional study evaluated a model constructed from data from 1 hospital and validated at 2 other hospitals. The primary endpoint was the ability of the model to predict CRC, as diagnosed by colonoscopy, from clinical characteristics. The secondary endpoint was to determine the percentage of patients who had CRC. RESULTS: Consecutive patients who were 45 years old or older and had self‐reported rectal bleeding for more than 1 week were evaluated. From January 2014 to July 2016, 362 patients answered a questionnaire and underwent colonoscopy. In the validation cohort, 56% of patients with rectal bleeding, weight loss, and changes in bowel habits had CRC, whereas 2% of patients with bleeding alone did. Overall, 18.2% of the patients had CRC, and 8.6% had adenomas. The proportion of CRC patients with potentially curable stage II or III disease was 74%, whereas the historical rate was 36%. The combination of rectal bleeding with both symptoms significantly predicted CRC in the validation set (odds ratio, 12.8; 95% confidence interval, 4.6‐35.4; P < .001). CONCLUSIONS: In low‐resource settings, patients with rectal bleeding, weight loss, and changes in bowel habits should be classified as high risk for CRC. Patients with a high risk score should be prioritized for colonoscopy to increase the number of patients diagnosed with potentially curable CRC. Cancer 2018;124:2766‐2773 . © 2018 American Cancer Society Abstract : Colorectal cancer is a growing public health problem in low‐ and middle‐income countries. This study, proving that a risk model can identify early‐stage patients, is the first prospective screening or surveillance colorectal cancer trial in sub‐Saharan Africa.